2012
DOI: 10.5430/jms.v3n3p11
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of E-Government Development: Some Methodological Issues

Abstract: Previous papers that have attempted to analyze the determinant factors of the implementation of e-government present serious limitations owing to multicollinearity and endogeneity problems.In this line, the aim of this paper is to analyze the factors which promote the development of the electronic administration in the national governments of 192 countries worldwide by simultaneous equations in order to overcome the cited problems.Our findings emphasize that there is a bidirectional relation between government… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
(48 reference statements)
1
4
0
Order By: Relevance
“…Their results indicated that governance in a country, e.g., political stability, regulatory quality or control of corruption, did not significantly contribute to its e-government maturity, and their relationship was not mediated by eparticipation. This conclusion is in line with prior research by García-Sánchez et al (2012). They analyzed the factors which promote the e-government development in the national governments using a more suitable econometric methodology.…”
Section: E-government Development Indicessupporting
confidence: 87%
See 1 more Smart Citation
“…Their results indicated that governance in a country, e.g., political stability, regulatory quality or control of corruption, did not significantly contribute to its e-government maturity, and their relationship was not mediated by eparticipation. This conclusion is in line with prior research by García-Sánchez et al (2012). They analyzed the factors which promote the e-government development in the national governments using a more suitable econometric methodology.…”
Section: E-government Development Indicessupporting
confidence: 87%
“…The existing models of e-government evolution suggest a linear progression from basic web publishing to fully integrated, advanced and matured e-government, where each successive stage of e-government is better than the previous one. Governments have to proceed through each stage (step) in a series (García-Sánchez et al, 2012;Krishnan et al, 2013). As for the development of egovernment services, the establishment of collective goals can be viewed as corresponding to the definition of resources available, and the way in which they may be allocated.…”
Section: Introductionmentioning
confidence: 99%
“…The four dimensions included in the research model are assumed to reflect the process of successful e-government implementation based on KM practices. The success of e-government projects depends on many factors like infrastructure, public employees, citizens and governments (Bataineh and Abu-Shanab, 2016;Tarhini et al, 2015;Garcia-Sánchez et al, 2012). This study will focus on the influence of KM practices on the success of e-government projects.…”
Section: Methodsmentioning
confidence: 99%
“…Information and communication technology (ICT) benefits businesses, industries, and government sectors (Ahn & Bretschneider, 2011; García‐Sánchez et al, 2012; Glyptis et al, 2020). Electronic government, also known as e‐government, is a manifestation of ICT implementation in the government sector.…”
Section: Introductionmentioning
confidence: 99%